2021
DOI: 10.1101/2021.02.23.21252276
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inequalities in the decline and recovery of pathological cancer diagnoses during the first six months of the COVID-19 pandemic: a population-based study

Abstract: Background: The restructuring of healthcare systems to cope with the demands of the COVID-19 pandemic has led to a reduction in clinical services such as cancer screening and diagnostics. Methods: Data from the four Northern Ireland pathology labs was used to assess trends in pathological cancer diagnoses from 1st March to 12th September 2020 overall and by cancer site, gender and age. These trends were compared to the same timeframe from 2017-2019. Results: Between 1st March and 12th September 2020 there … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Infectious diseases may change the model of clinical services, especially in cancer screening, diagnostics, and treatment [ 31 ]. A prospective cohort study that compared the epidemiology, clinical features and outcomes of influenza A (H1N1) 2009 pneumonia between the pandemic period and the first post-pandemic influenza season showed that patients during the post-pandemic period were older and more likely to have chronic obstructive pulmonary disease, chronic kidney disease and cancer than the others [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Infectious diseases may change the model of clinical services, especially in cancer screening, diagnostics, and treatment [ 31 ]. A prospective cohort study that compared the epidemiology, clinical features and outcomes of influenza A (H1N1) 2009 pneumonia between the pandemic period and the first post-pandemic influenza season showed that patients during the post-pandemic period were older and more likely to have chronic obstructive pulmonary disease, chronic kidney disease and cancer than the others [ 32 ].…”
Section: Discussionmentioning
confidence: 99%